Aspirin in the Food and Drug Administration Adverse Event Reporting System: Missing Demographics and Underreporting - Serebruany, Victor L.; Tomek, Ales; Kim, Moo Hyun; Litvinov, Oleg; Marciniak, Thomas A. (TH Open, 2017)
Background The U.S. Food and Drug Administration (FDA) Adverse Event (AE) Reporting System (FAERS) is a global passive surveillance repository requiring mandatory updates by pharmaceutical manufacturers. Oral antiplatelet agents (OAAs) including aspirin (acetylsalicylic acid [ASA]) are broadly used to prevent thrombosis, at the expense of extra bleeding risks. However, the OAA filing quality and their comparative patterns in FAERS are unknown. We assessed completeness of original annual FAERS reports for OAA with special attention on ASA.Methods We extracted AE cases co-reported with OAA including ASA, clopidogrel, prasugrel, ticagrelor, vorapaxar, or their combination. The 2015 FAERS cases were examined based on OAA distribution, suspected causative role, missing gender or age, and most common AEs after ASA.Results A total of 1,187,729 reports qualified the inclusion criteria. The majority (n = 1,121,989) of the reports contain no reference of OAA, while 65,730 reports contain reference of at least one OAA, including 47,900 ASA cases. Therapy with ASA was heavily (>50%) underreported when used with prasugrel or ticagrelor, but still dominant (72.8%) among OAAs, followed by clopidogrel (18.7%), prasugrel (4.1%), ticagrelor (3.6%), and anecdotal vorapaxar (0.05%). Despite current recommendations, some (0.73%) reports contain multi-OAAs. The primary role of ASA in AE reporting was seldom (<1%), followed by clopidogrel (2.9%), prasugrel (3.7%), and highest for ticagrelor (9.3%). Missing gender after OAA was not common (<10%), but age was missing in approximately 25% of reports. Bleeding was the most frequent AE associated with ASA.Conclusion The quality of reporting for OAA in general and ASA in particular can be improved by stricter FDA rules, better surveillance, and enforcements. Heavy ASA underreporting during dual antiplatelet therapy and missed demographic variables challenge outcome research capacities for establishing drug interactions in FAERS.
Keywords: aspirin; antiplatelet agents; adverse events; safety; registry